2016
DOI: 10.1007/s10904-016-0481-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Eu3+-Doped Aluminophosphate Glass with a High Concentration of Silver and Tin

Abstract: last decades in search of improvements in the luminescent properties of europium given its relevance for optical device applications [1][2][3][4][5][6][7][8][9][10][11][12][13]. Malta et al. [1] irst reported that an improved photoluminescence (PL) of Eu 3+ ions in glass containing Ag nanoparticles (NPs) occurred due to the surface plasmon resonance (SPR) of the silver particles.Other groups subsequently concluded similarly on the role of local-ield efects of plasmonic Ag particles amplifying Eu 3+ PL in glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…2) since 320 nm is resonant with exciting the 7 F 0 -5 H 4 transition in Eu 3+ . 17,25 Thus Eu 2+ /Eu 3+ co-doping facilitated by C ND introduction in the melt, yields tunable colored emission with color coordinates presented in the CIE diagram, Fig. 4 inset.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2) since 320 nm is resonant with exciting the 7 F 0 -5 H 4 transition in Eu 3+ . 17,25 Thus Eu 2+ /Eu 3+ co-doping facilitated by C ND introduction in the melt, yields tunable colored emission with color coordinates presented in the CIE diagram, Fig. 4 inset.…”
Section: Resultsmentioning
confidence: 96%
“…2(a) shows the optical transmission spectra obtained for the various glasses under consideration. The Eu glass exhibits the dip in the transmission spectrum around 393 nm due to 7 F 0 -5 L 6 transition of Eu 3+ ions, 16,17 while the host absorption edge characterizes the decreased transmission toward shorter wavelengths. 9 It is observed for the EuND1 glass that a decreased transmission developed around 320 nm while the glass appears to have the transmission edge shifted towards shorter wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the two fold coordinated Sn in SiO 2 and borate glass shows two emission bands: a-band [singlet (S 1 )-singlet (S 0 )] and b-band [triplet (T 1 )-singlet (S 0 )] and the Sn in phosphate glass just shows an emission band [triplet (T 1 )-singlet (S 0 )]. [29][30][31] Based on the above facts, we put forward that the shorter wavelength emission band around 432 nm can be mainly attributed to the S 1 -S 0 transition and the longer wavelength emission band around 520 nm can be ascribed to the T 1 -S 0 transition. Compared with Sn 2+ -doped 60ZnO-40P 2 O 5 glass, 27,32 the broadband luminescence of the SSP0 glass is in the visible wavelength range, which could be a new light source.…”
Section: Structural Analysismentioning
confidence: 91%
“…8,[24][25][26] The heat treated samples present an absorption band centered around 420 nm, which is attributed to the SPR associated with the metallic Ag NPs. 8,18,27,28 Top insets present the SPR absorption intensity at 420 nm as a function of HT time, which increases with longer HT times and a higher temperature for both glass compositions. Furthermore, the samples doped with higher europium concentrations exhibit a higher rate for the intensity increase in SPR absorption compared to samples with a lower europium content indicating a higher density of Ag NPs, which agrees with the behavior reported by Jiao et al 27 The results indicate the incorporation of Eu and Ag ions in the host as well as the HT process promotes the precipitation of metallic Ag NPs.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…Other reports also ascribe the RE luminescence enhancement to the energy transfer process from intermediate Ag species (isolated Ag + or Ag NCs) to RE ions instead of SPR contribution. 8,[16][17][18][19] Thus, the actual interaction mechanism between Ag species and RE ions is a controversial and unclear question, which requires further signicant investigation.…”
Section: Introductionmentioning
confidence: 99%